PT. Garuda Indonesia's Strategy in Responding to the Increase in Airfare Prices (Quantitative Content Analysis Study on kompas.com and liputan6.com for the August 2nd until September 2nd 2022 Period) - Setyowati, Nurul; Purworini, Dian (Universitas Muhammadiyah Surakarta, 2022)
Purpose: Through quantitative content analysis using Situational Crisis Communication Theory, this study aims to find out what response strategies were carried out by PT Garuda Indonesia in regard to the increase in airfare prices on the Kompas.com and Liputan6.com news pages for the 2 August to 2 September 2022 period. Methodology: By evaluating content validity and inter-coding reliability, this study uses a quantitative descriptive content analysis. The subjects of this study are all articles about PT Garuda Indonesia's response to the increase in airfare prices that appeared on Kompas.com and Liputan6.com between 2 August until 2 September 2022. Results: The results show that Garuda's management response strategy which is published in 39 news articles is quite good. Garuda is more dominant, using the primary crisis responses strategy by diminishing the issue. The responses are carried out by the company to minimize the damage caused by the crisis. Applications/Originality/Value: This study can be used to add recommendations for institutions that face the same problems by using the responses strategy carried out by the airline company PT Garuda Indonesia through online media coverage. The difference in this study lies in the object of research, the theoretical analysis used, the measuring instruments, and the literature in the study.